1998
DOI: 10.1159/000020548
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Confocal Epi-Reflection and Fluorescence Microscopy of the Rat Kidney in vivo

Abstract: To visualize superficial and accessible renal tubule cells functioning in situ and to relate what we can ‘see’ to what we know of their function from more invasive in vivo or less direct in vitro studies means applying and adapting recent advances in epifluorescence and confocal microscopy to improve image resolution and to combine this with the use of fluorescent labels to monitor the handling of specific molecules by the proximal and distal renal tubule cells in vivo. Doing this in living tissue is novel, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Intracellular concentrations of three to five times the medium concentration were determined (142). Fluorescein accumulation in proximal tubules during secretory transport has been confirmed in rat kidney in vivo (143). Confocal microscopic images of rat proximal tubule cells showed that fluorescein was compartmentalized within subcellular organelles, predominantly in mitochondria.…”
Section: Intracellular Dispositionmentioning
confidence: 82%
“…Intracellular concentrations of three to five times the medium concentration were determined (142). Fluorescein accumulation in proximal tubules during secretory transport has been confirmed in rat kidney in vivo (143). Confocal microscopic images of rat proximal tubule cells showed that fluorescein was compartmentalized within subcellular organelles, predominantly in mitochondria.…”
Section: Intracellular Dispositionmentioning
confidence: 82%
“…In the kidney, the capillary network of the glomerulus (50) and its circulation (70) have been studied. Boyde et al (15) were able to visualize individual red blood cells and white blood cells as they flowed through the peritubular capillary circulation near the surface of living kidneys. However, the maximum depth of focus for all of these studies is Ͻ1 mm and, consequently, in a whole kidney that has greater tissue depth, continuous measurement from the arterial trunk to the downstream capillaries has not been possible.…”
Section: Three-dimensional Analysis Of Serial Sectionsmentioning
confidence: 99%
“…Second, organ movements caused by microcirculation and respiration may create problems, especially at higher magnifications. Few organs have been visualized by this technique: brain [8], spleen [9], skin [10], cornea [11], lung [12], and kidney [13]and most of them for studies of morphological changes and hemodynamics in the intact organ. Recently, Dunn et al [14]successfully studied the dynamics of receptor-mediated endocytosis in intact kidney by two-photon laser scanning microscopy (TPLSM) demonstrating individual endosomes containing fluorescence-labeled dextran and gentamicin.…”
Section: Introductionmentioning
confidence: 99%